Mechanical stimulation improves rotator cuff tendon-bone healing via activating IL-4/JAK/STAT signaling pathway mediated macrophage M2 polarization - Liu, Yuqian; Wang, Linfeng; Li, Shengcan; Zhang, Tao; Chen, Can; Hu, Jianzhong; Sun, Deyi; Lu, Hongbin (Journal of orthopaedic translation, 2022)
It is well known that appropriate mechanical stimulation benefits tendon-bone (T-B) healing, however, the mechanisms behind this are still uncovered completely. Here, we aimed to explore whether the IL-4/JAK/STAT signaling pathway mediated macrophage polarization was involved in mechanical stimulation induced T-B healing. C57BL/6 mice rotator cuff (RC) repair model was established, and the mice were randomly allocated to the following group. 1. Mice were allowed for free cage activities after surgery (FC group); 2. Mice received treadmill running initiated on postoperative day 7 (TR group); 3. Mice only received a local injection of hydrogel containing IL-4 neutralizing antibody without postoperative intervention (FC ​+ ​AF-404-SP group); 4. Mice received a local injection of hydrogel containing IL-4 neutralizing antibody and postoperative treadmill running (TR ​+ ​AF-404-SP group). The expression of IL-4 within supraspinatus tendon (SST) enthesis was measured by Enzyme-linked immunosorbent assay (ELISA). In addition, the activation of JAK/STAT signaling pathway in macrophages and identification of macrophage phenotype at the RC insertion site was detected by Flow cytometry and qRT-PCR. T-B healing quality in this RC repair model was evaluated by histological staining, Micro-computed tomography (Micro-CT) scanning, and biomechanical testing. In this study, using the RC repair model, we confirmed that generation of IL-4, activation of the JAK/STAT signaling pathway in macrophages, the ability of macrophages to polarize towards M2 subtype, and T-B healing quality were significantly enhanced in TR group compared to FC group. When comparing FC ​+ ​AF-404-SP group with TR ​+ ​AF-404-SP group, it was found that the mechanical stimulation induced this effect was depleted following the blockade of the IL-4/JAK/STAT signaling pathway. Our finding suggested that mechanical stimulation could accelerate T-B healing via activating the IL-4/JAK/STAT signaling pathway that modulates macrophages to polarize towards M2 subtype. This is the first study to reveal a significant role of mechanical stimulation in the IL-4/JAK/STAT signaling pathway activation and macrophage polarization during RC T-B healing, which highlights the IL-4/JAK/STAT signaling pathway as a potential target to mediate macrophage M2 polarization and improves T-B healing for RC repair.